Evaluasi dan Pengendalian Strategik: Proses, Kerangka Kerja, dan Studi Kasus - Fahrurrozi Fahrurrozi (CV. Ulil Albab Corp, 2024)
Abstract: This study aims to find out how the flow of strategy evaluation in the case of the Company to achieve a company's vision goals, this research method uses qualitative descriptive research, Data collection techniques using observation, interviews, and documentation. Data analysis techniques used library research approach The decisive factors in Strategy Evaluation are carried out with the approach: 1). Consistency, 2). Consonants, 3) Feasibility, 4) Excellence. Basic Organizational Strategy, Organizational Performance, Corrective Action Effective strategy evaluation enables an organization to maximize the benefits of internal strengths as they develop, to maximize the benefits of external opportunities as they arise, to recognize and defend against threats, and to minimize internal weaknesses before they cause damage.